Failure to down-regulate the epithelial sodium channel causes salt-sensitivity in Hsd11b2 heterozygote mice - Craigie, Eilidh (2012)
In vivo, the enzyme 11β-hydroxysteroid dehydrogenase type 2 influences ligand access to the mineralocorticoid receptor. Ablation of the encoding gene, HSD11B2, causes the hypertensive syndrome of Apparent Mineralocorticoid Excess. Studies in humans and experimental animals have linked reduced 11β-hydroxysteroid dehydrogenase type 2 activity and salt-sensitivity of blood pressure. In the present study, renal mechanisms underpinning salt-sensitivity were investigated in Hsd11b2(+/−) mice fed low, standard and high sodium diets. In wild-type mice, there was a strong correlation between dietary sodium content and fractional sodium excretion, but not blood pressure. High sodium feeding abolished amiloride-sensitive sodium reabsorption, consistent with down-regulation of the epithelial sodium channel. In Hsd11b2(+/−) mice, the natriuretic response to increased dietary sodium content was blunted and epithelial sodium channel activity persisted. High sodium diet also reduced renal blood flow and increased blood pressure in Hsd11b2(+/−) mice. Aldosterone was modulated by dietary sodium in both genotypes and salt-sensitivity in Hsd11b2(+/−) mice was associated with increased plasma corticosterone levels. Chronic administration of an epithelial sodium channel blocker or a glucocorticoid receptor antagonist prevented salt-sensitivity in Hsd11b2(+/−) mice, whereas mineralocorticoid receptor blockade with spironolactone did not. This study shows that reduced 11β-hydroxysteroid dehydrogenase type 2 causes salt-sensitivity of blood pressure due to impaired renal natriuretic capacity. This reflects deregulation of epithelial sodium channels and increased renal vascular resistance. The phenotype is not caused by illicit activation of mineralocorticoid receptors by glucocorticoids, but by direct activation of glucocorticoid receptors.